Feminist utopian literature: the origins of the genre - Жаданов, Юрий Анатольевич; Жаданова, Татьяна Владимировна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The article deals with the processes of origin and development of female utopian literature. Three main stages of the evolution of the genre are distinguished. The first stage was studied - the era of the XVII - XVIIІ centuries. Particular attention is paid to Cary, M. Cavendish and S. Scott’s works. Their key works have been analyzed. The basic genre features of the new literary phenomenon are distinguished, the revealed differences from the products of the traditional male utopia are revealed.